Literature Review Pengaruh Water Safety Plan (WSP) dalam Meningkatkan Kualitas Pengelolaan Air untuk Masyarakat Sehat - Murni Noviani Nasution (Pusat riset dan Inovasi Nasional, 2025)
This study aims to analyze the impact of implementing the Water Safety Plan (WSP) in improving water management quality for the creation of a healthy society. The Water Safety Plan (WSP) is a systematic approach designed to ensure that the water supplied to the community is safe and poses no risk to health. This research utilizes a literature review method, examining various previous studies on the implementation of WSP in different countries and its impact on water quality management. The findings show that the implementation of WSP can enhance water management more effectively by identifying potential risks early and ensuring continuous water quality control. Therefore, the application of WSP is crucial to achieving safe and potable water quality, which in turn can improve public health.